The acute effect of cigarette smoking on the high-sensitivity CRP and fibrinogen biomarkers in chronic obstructive pulmonary disease patients. (April 2013) - van Dijk, Wouter D; Akkermans, Reinier; Heijdra, Yvonne; Weel, Chris van; Schermer, Tjard RJ; Scheepers, Paul TJ; Lenders, Jacques WM
Aim: The evidence on the acute effects of smoking on biomarkers is limited. Our aim was to study the acute effect of smoking on disease-related biomarkers.Methods: The acute effect of smoking on serum high sensitivity CRP (hs-CRP) and plasma fibrinogen and its association with disease severity was studied by challenging 31 chronic obstructive pulmonary disease patients with cigarette smoking and repeatedly measuring these biomarkers before and after smoking.Results: Fibrinogen and hs-CRP increased directly after smoking by 9.4 mg/dl (95% CI: 4.2–14.5) and 0.13 mg/l (95% CI: 0.03–0.23), respectively. Fibrinogen levels remained elevated after 35 min, whereas hs-CRP normalized. Pearson's correlation coefficient between the hs-CRP change and chronic obstructive pulmonary disease severity was 0.25 (p = 0.06).Conclusion: Fibrinogen and hs-CRP increased directly after smoking in the chronic obstructive pulmonary disease patients. Their association with disease risk and/or progression remains to be demonstrated.